2019
DOI: 10.1002/lary.28408
|View full text |Cite
|
Sign up to set email alerts
|

Piezosurgery versus conventional osteotomy in rhinoplasty: A systematic review and meta‐analysis

Abstract: Objective: Piezosurgery, used in different otolaryngology procedures, was a breakthrough in surgery. We systematically reviewed the differences in outcomes after lateral nasal osteotomy with peizosurgery and conventional osteotome and quantified the differences through a meta-analysis.Methods: Medline, Embase, and Cochrane library databases were selected to search for randomized clinical trials (RCTs) published before January 2019 that detailed differences between piezosurgery and conventional osteotomy. The k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Postoperative pain is an early and annoying complication of septorhinoplasty, and its primary etiology is osteotomy 33 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative pain is an early and annoying complication of septorhinoplasty, and its primary etiology is osteotomy 33 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain is an early and annoying complication of septorhinoplasty, and its primary etiology is osteotomy 33 33 . Thus, many techniques, instruments, and agents have been used to reduce postoperative pain following septorhinoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis from 2019. published by Mirza et al proved that PEI causes less ecchymosis, edema and pain than conventional osteotomy, without extending the duration of surgery. It included six randomized clinical trials from 2015. to 2019. and additionaly proved that PEI has no longer duration in surgery, unlike some previous trials have suggested [13]. The study by Otake et al was the first to prove the clinical advantage of PEI in the soft tissue [14].…”
Section: Casementioning
confidence: 97%
“…Recently, a much-needed meta-analysis was published. 13 A total of six randomized, controlled trials were identified and accepted for meta-analysis. Evaluation for key outcomes such as edema, bruising, pain, and time of operation was performed.…”
Section: The Difficult Nasal Bonesmentioning
confidence: 99%